George W. Cothran, The Revised Statutes of the State of Illinois, Embracing All Laws of a General Nature in Force July 1, 1883, with Notes and References to Judicial Decisions Construing their Provisions Page 453, § 56 - (:unkn) unknown (General Publisher, 1879)
Prohibited the concealed carry of any pistol, knife, slungshot, knuckles of brass, steel, iron, or other deadly weapons. Also prohibited brandishing said weapons. Violators fined not exceeding one hundred dollars.
--
Keywords: BRANDISHING